New EM parameter estimation algorithm for a type of micro-motion SFM signal - Yong-yan JIANG; Shi-yuan ZHANG (Tongxin xuebao)
Aiming at the problem that the existing method has high computational complexity and high SNR,a novel method of multi-component SFM signals parameter estimation based on EM algorithm was proposed as to spinning tar-get's narrow band micro-motion echoes.The echo model of spinning target and its micro-doppler measurements based on time-frequency analysis were given.The iterative parameter estimation steps based on Gaussian mixture model and EM algorithm to measurements were established.The simulation results demonstrate that when SNR is greater than -3 dB and the SFM components are equal or greater than 2，the method can estimate the target’s micro-motion parameters e.g.projection size accurately in narrow band condition.